Reimagining the Transition to Residency: A Trainee Call to Accelerated Action. (8th March 2022) - Lin, Grant L.; Guerra, Sylvia; Patel, Juhee; Burk-Rafel, Jesse
Abstract : The transition from medical student to resident is a pivotal step in the medical education continuum. For applicants, successfully obtaining a residency position is the actualization of a dream after years of training and has life-changing professional and financial implications. These high stakes contribute to a residency application and Match process in the United States that is increasingly complex and dysfunctional, and that does not effectively serve applicants, residency programs, or the public good. In July 2020, the Coalition for Physician Accountability (Coalition) formed the Undergraduate Medical Education-Graduate Medical Education Review Committee (UGRC) to critically assess the overall transition to residency and offer recommendations to solve the growing challenges in the system. In this Invited Commentary, the authors reflect on their experience as the trainee representatives on the UGRC. They emphasize the importance of trainee advocacy in medical education change efforts; reflect on opportunities, concerns, and tensions with the final UGRC recommendations (released in August 2021); discuss factors that may constrain implementation; and call for the medical education community—and the Coalition member organizations in particular—to accelerate fully implementing the UGRC recommendations. By seizing the momentum created by the UGRC, the medical education community can create a reimagined transition to residency that reshapes its approach to training a more diverse, competent, and growth-oriented physician workforce.